Understanding the prion-like behavior of mutant p53 proteins in triple-negative breast cancer pathogenesis: The current therapeutic strategies and future directions - Naeimzadeh, Yasaman; Tajbakhsh, Amir; Fallahi, Jafar (Heliyon, 2024)
Breast cancer (BC) is viewed as a significant public health issue and is the primary cause of cancer-related deaths among women worldwide. Triple-negative breast cancer (TNBC) is a particularly aggressive subtype that predominantly affects young premenopausal women. The tumor suppressor p53 playsa vital role in the cellular response to DNA damage, and its loss or mutations are commonly present in many cancers, including BC. Recent evidence suggests that mutant p53 proteins can aggregate and form prion-like structures, which may contribute to the pathogenesis of different types of malignancies, such as BC. This review provides an overview of BC molecular subtypes, the epidemiology of TNBC, and the role of p53 in BC development. We also discuss the potential implications of prion-like aggregation in BC and highlight future research directions. Moreover, a comprehensive analysis of the current therapeutic approaches targeting p53 aggregates in BC treatment is presented. Strategies including small molecules, chaperone inhibitors, immunotherapy, CRISPR-Cas9, and siRNA are discussed, along with their potential benefits and drawbacks. The use of these approaches to inhibit p53 aggregation and degradation represents a promising target for cancer therapy. Future investigations into the efficacy of these approaches against various p53 mutations or binding to non-p53 proteins should be conducted to develop more effective and personalized therapies for BC treatment. The role of Prion-like Behavior of Mutant p53 Proteins in Triple-Negative Breast Cancer Pathogenesis. [Display omitted] •Mutant p53 forms prion-like structures in breast cancer, especially TNBC.•Targeting p53 aggregation is key in TNBC therapy.•Diverse approaches (e.g., chaperone inhibitors, aggrephagy-based approaches, immunotherapy, gene therapy, and CRISPR-Cas9) target p53 aggregates.•Zinc metallochaperones (e.g., ZMC1) and small molecules (e.g., PRIMA-1 and APR-246) show promise in restoring mutant p53 function.